2021
DOI: 10.1097/mbp.0000000000000556
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone based blood pressure measurement: accuracy of the OptiBP mobile application according to the AAMI/ESH/ISO universal validation protocol

Abstract: The aim of this study was to assess the accuracy of the OptiBP mobile application based on an optical signal recorded by placing the patient's fingertip on a smartphone's camera to estimate blood pressure (BP). Measurements were carried out in a general population according to existing standards of the Association for the Advancement of Medical Instrumentation (AAMI), the European Society of Hypertension (ESH) and the International Organization for Standardization (ISO).Methods Participants were recruited duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 15 publications
(19 reference statements)
0
47
0
Order By: Relevance
“…The sample size of all articles analyzed in this review ranged between three and 3000 subjects. Six articles used a sample size smaller than 10 subjects 18 , 24 , 25 , 29 , 31 , 32 , and 8 articles used sample sizes of 85 or more subjects 9 , 11 , 14 , 16 , 22 , 23 , 28 , 33 (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample size of all articles analyzed in this review ranged between three and 3000 subjects. Six articles used a sample size smaller than 10 subjects 18 , 24 , 25 , 29 , 31 , 32 , and 8 articles used sample sizes of 85 or more subjects 9 , 11 , 14 , 16 , 22 , 23 , 28 , 33 (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, structural differences in the cardiovascular system, such as gender-dependent diameters of blood vessels or different average heart rates between genders 35 , 36 , and differing skin thickness between women and men, also have a direct impact on the PPG signal 37 . In this review, 14 of the 25 articles reported the ratio of female to male participants 9 12 , 15 17 , 19 , 21 , 23 26 , 33 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Formulae for the polar coordinates, which differ from standard Cartesian-polar conversion, are described in Critchley et al [33]. SBP systolic blood pressure; MBP mean blood pressure; DBP diastolic blood pressure; BP inv BP as assessed by the invasive method; BP PPG BP as assessed by the non-invasive (PPG) method; ∆BP change in BP of at least ± 15% ◂ context that was not found in the final use-case of the investigated smartphone app [21,22]. Additionally, no population stratification has been done and so more investigation should be conducted to validate such technology in relevant population.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a smartphone application based on PWA (OptiBP™, Biospectal, Switzerland) has been validated on a general population compared to a dual-head stethoscope and sphygmomanometer method as described in ISO 81060-2 standards, and in various other settings [21][22][23][24]. Although the ISO universal standard may validate the accuracy and precision of the above solution, its ability to track intra-patient BP variations remains to be validated [25].…”
Section: Introductionmentioning
confidence: 99%